(Table 1) Geochemical composition of surface waters obtained aboard the R/V Rift along the Volga-Caspian canal - E L Vinogradova; Peter Makkaveev; Z G Melnikova; Yuri Nalbandov; Pavel A Stunzhas; P V Khlebopashev (PANGAEA, 2011)
The Volga River discharge consists of the waters transferred by fast currents through channels and the waters which are passing through the shallow areas of the delta overgrown by cane. Using the hydrochemical data, it is possible to track distribution of the waters modified by extquotesinglebiofilters extquotesingle of macrophytes in the delta shallows starting from the external edge of the delta. The main distinctive features of these waters are the high content of dissolved oxygen, the abnormally high values of the pH, and the low content of dissolved inorganic carbon (both total and as CO2). These waters extend in the shape of 1 to 3-km-wide strips at a distance of 20-40 km from the outer border of the delta. The analysis of the data obtained during the expeditions run by the Institute of Oceanology of the Russian Academy of Sciences in 2003-2009, along with archived and published data, show that such extquotesinglemodified extquotesingle waters occur almost constantly along the outer edge of the Volga River delta.
Supplement to: Vinogradova, EL et al. (2011): On the transformation of the chemical composition of the Volga River discharge waters at the Caspian shallows. Oceanology, 51(5), 796-803, https://doi.org/10.1134/S0001437011050213